Emergency department utilisation by patients with a diagnosis of borderline personality disorder: An acute response to a chronic disorder. (30th March 2022) - Broadbear, Jillian H; Rotella, Joe‐Anthony; Lorenze, Donna; Rao, Sathya
Abstract: Objective: Patients with borderline personality disorder (BPD) are likely to attend the ED while experiencing crises and associated self‐injury and suicidality. Our study describes the prevalence, features, and outcomes associated with ED presentations by patients diagnosed with BPD in Outer Eastern Melbourne, Australia. Methods: A retrospective electronic audit of 157 364 ED attendances identified 700 unique BPD‐related ED presentations between May 2015 and April 2016. For the purpose of comparison, 583 (81% female) of these 700 cases were matched with 'depression only' cases. ED re‐presentation data were also extracted. Results: The 583 matched BPD patients attended ED a total of 2807 times during the audit year compared with 1092 attendances for matched depression‐only patients. BPD patients were more likely to: arrive by ambulance (50%); have comorbid substance abuse (44%); have a psychotic (15%) or bipolar disorder (17%); be under the care of a psychiatrist (31%); be case‐managed (42%); and be admitted to an inpatient unit (21%). ED doctors saw 38% of BPD or depression patients within the recommended time according to their triage category. The majority (73%) of BPD patients attended ED more than once during the audit year (average 4.81 ± 6.63 times; range 2–78). Conclusion: Repeated ED attendance of a subset of patients diagnosed with BPD highlights both the severity of their presentation and the inadequacy of community mental health services for meeting their complex needs. Development of effective ED referral pathways with follow‐up to engage patients in BPD‐appropriate treatment will reduce the likelihood of crises and reliance on hospital EDs for acute episodic care.